In vitro characterization and genome sequencing of two novel lytic phages against Salmonella Infantis isolated from poultry feces - Battistelli, Noemi; Tittarelli, Fabrizia; Ruffini, Fausto; Gavazzi, Luigi; Scattolini, Silvia; Acciari, Vicdalia Aniela; Romualdi, Teresa; Curini, Valentina; Di Carlo, Simona; D’Alterio, Nicola; Migliorati, Giacomo; Pomilio, Francesco; et al. (Frontiers in Microbiology, 2024)
IntroductionSalmonella spp. is the second most common bacteria associated with foodborne gastrointestinal outbreaks in humans, with the highest contamination levels in meat, especially poultry. Salmonella enterica subsp. enterica serovar Infantis is the primary serovar isolated from broilers, without causing any symptomatic disease. Conversely, certain human strains can result in symptomatic illness (fever, headache, and diarrhoea). Therefore, reducing S. Infantis colonization in broilers is important before slaughter, to prevent this pathogen carryover along the food chain.MethodsHere, we report the characterization of two S. Infantis virulent phages, isolated from broiler feces. Isolates were phenotypically and genetically characterized.Results and discussionPhages (ɸ) SaI_NFG_5581 and SaI_NFG_5577 were characterized as strictly lytic versus S. Infantis but with different bacteriolytic activities and genetic features. They both belong to the Caudoviricetes class, but ɸSaI_NFG_5581 (genome length 112,970 bp) belongs to the Demerecviridae family while ɸSaI_NFG_5577 (genome length 42,481 bp) to the Guernseyvirinae family. Genomic analysis excluded the presence of lysogeny, toxin, or antimicrobial resistance genes, and for those reasons, the two phages could be considered safe. Phages are stable under a broad range of pH (4-10) and temperature (4°C-50°C) conditions. In vitro, both ɸSaI_NFG_5581 and ɸSaI_NFG_5577 were able to lower Salmonella counts of about 2.2 LOG/mL and 3.4 LOG CFU/mL respectively, at MOI 0.1 after 2 h of treatment. After 24 h, Salmonella counts treated with both phages remained lower than the control (non-phage-treated Salmonella). These newly isolated phages have promising features, which could be exploited and further studied for potential in vivo application.